The money tree - Stewart, Sarah; Small, David (New York : Farrar, Straus, and Giroux, 1991)
In summer the leaves on the strange tree growing in Miss McGillicuddy's yard are harvested by many people, but when Miss McGillicuddy thinks about needing firewood for the winter, she realizes the tree may have another use.
Keywords: Money -- Fiction; Trees -- Fiction; Seasons -- Fiction